A new polytypic species of yellow-shouldered bats, genus Sturnira (Mammalia: Chiroptera: Phyllostomidae), from the Andean and coastal mountain systems of Venezuela and Colombia - Molinari, Jesús; Bustos, Xiomar E.; Burneo, Santiago F.; Camacho, M. Alejandra; Moreno, S. Andrea; Fermín, Gustavo (Zootaxa, 2017)
Sturnira is the most speciose genus of New World leaf-nosed bats (Phyllostomidae). We name Sturnira adrianae, new species. This taxon is born polytypic, divided into a larger subspecies (S. a. adrianae) widespread in the mountains of northern and western Venezuela, and northern Colombia, and a smaller subspecies (S. a. caripana) endemic to the mountains of northeastern Venezuela. The new species inhabits evergreen, deciduous, and cloud forests at mainly medium (1000–2000 m) elevations. It has long been confused with S. ludovici, but it is more closely related to S. oporaphilum. It can be distinguished from other species of Sturnira by genetic data, and based on discrete and continuously varying characters. Within the genus, the new species belongs to a clade that also includes S. oporaphilum, S. ludovici, S. hondurensis, and S. burtonlimi. The larger new subspecies is the largest member of this clade. The two new subspecies are the most sexually dimorphic members of this clade. The smaller new subspecies is restricted to small mountain systems undergoing severe deforestation processes, therefore can be assigned to the Vulnerable (VU) conservation category of the International Union for Conservation of Nature (IUCN).